Predicting Hepatitis B Virus (HBV) Surface Antigen Seroclearance in HBV e Antigen–Negative Patients With Chronic Hepatitis B: External Validation of a Scoring System. (27th November 2014) - Liu, Jessica; Tseng, Tai-Chung; Yang, Hwai-I; Lee, Mei-Hsuan; Batrla-Utermann, Richard; Jen, Chin-Lan; Lu, Sheng-Nan; Wang, Li-Yu; You, San-Lin; Chen, Pei-Jer; Chen, Chien-Jen; Kao, Jia-Horng
Abstract: Background.  Hepatitis B virus (HBV) surface antigen (HBsAg) seroclearance is the ultimate serological end point in chronic hepatitis B. This study aimed to develop and validate a prediction score for spontaneous HBsAg seroclearance in HBV e antigen (HBeAg)-negative patients with chronic hepatitis B due to HBV genotype B or C. Methods.  The development cohort included 2491 untreated participants from the community-based REVEAL-HBV study, who were HBeAg negative, anti–hepatitis C virus negative, and cirrhosis free. The independent validation cohort consisted of 1934 hospital-based individuals from the National Taiwan University Hospital. Clinical markers included in the model were age and serum HBV DNA and HBsAg levels. Cox proportional hazards regression models were used to create the prediction model. Results.  A prediction score ranging from 0 to 27 was developed. Predicted probabilities of 5- and 10-year HBsAg seroclearance ranged from 0.95% to 30.49% and from 2.58% to 62.52%, respectively. When applied to the independent validation cohort, the areas under the receiver operating characteristic curves for the 5- and 10-year prediction of HBsAg seroclearance in the validation cohort were 0.82 (95% confidence interval [CI], .76–.88) and 0.74 (95% CI, .70–.78). Model fit was still adequate, according to Hosmer–Lemeshow goodness of fit tests. Conclusions.  A clinically applicable prediction score for HBsAg seroclearance was developed and externally validated. This model can assist clinicians in further stratifying risk groups.